2021
DOI: 10.1136/bcr-2020-241061
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis pneumonia causing cavitating lung nodules in an immunocompetent individual

Abstract: Pneumocystis jirovecii pneumonia (PCP) is a potential life-threatening pulmonary infection which commonly manifests in immunosuppressed patients especially with HIV, with underlying malignancies, severe malnutrition as well as those on immunosuppressive treatments. There have been case reports of symptomatic PCP in individuals with a normally functioning immune system with typical clinical features and radiologic findings of bilateral and diffuse interstitial opacities. However, PCP in immunocompetent individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In literature, PCP is uncommon in immunocompetent subjects. 6 , 7 More rarely, few cases have been reported in immunocompetent without any underlying diseases like our patient.…”
Section: Discussionmentioning
confidence: 63%
“…In literature, PCP is uncommon in immunocompetent subjects. 6 , 7 More rarely, few cases have been reported in immunocompetent without any underlying diseases like our patient.…”
Section: Discussionmentioning
confidence: 63%
“…This patient also had one out of three AFB cultures positive for Mycobacterium avium complex, which was thought to be a contaminant. A second case involved an immunocompetent patient who presented with non-productive cough and dyspnoea 10. Imaging revealed multiple cavitary pulmonary nodules.…”
Section: Discussionmentioning
confidence: 99%
“…The most significant risk factors for PCP in HIV-free patients are the use of glucocorticoids and the presence of cell-mediated immune defects, which lead to changes in lung surfactant, thus predisposing the patient to pneumonia [41]. Previous studies have documented PCP in immunocompetent individuals [42][43][44][45][46]. A case of PCP in a non-HIV-infected Indian patient who has not undergone previous glucocorticoid treatment was described by Koshy et al (2015) [42].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports of PCP in patients without underlying immunosuppressive disease. A study by Kano et al described five patients who developed PCP without any underlying immunosuppressive conditions, and in their literature review, they identified only 11 other reported cases [44]. However, the exact mechanisms that lead to the development of PCP in patients without evidence of immunosuppressive status remain unclear [45].…”
Section: Discussionmentioning
confidence: 99%